Andrographolide Inhibits Cholangiocarcinoma Cell Migration by Down-Regulation of Claudin-1 via the p-38 Signaling Pathway - Pearngam, Phorutai; Kumkate, Supeecha; Okada, Seiji; Janvilisri, Tavan (Frontiers in Pharmacology, 2019)
Andrographolide, a bioactive phytochemical from Andrographis paniculata, is emerging as a promising anti-cancer agent against various cancers. This study aims to investigate anti-cancer activities of andrographolide against cholangiocarcinoma (CCA) and to understand the underlying mechanism. Anti-proliferative activity of andrographolide was evaluated in a range of CCA cell lines including HuCCA-1, KKU-100, KKU-M213, and RMCCA-1. The anti-migration activity and the corresponding mechanism was studied in highly metastatic KKU-M213 cells. The results indicated that andrographolide significantly inhibited the proliferation of CCA cells with the 50% inhibitory growth concentration (IC50) of ~120 µM. Andrographolide also inhibited CCA cell migration and invasion. Our further explorations demonstrated that andrographolide decreased the expression of Claudin-1, a major tight junction protein, while up-regulated the expression of Snail, a transcriptional repressor of claudin-1. Moreover, andrographolide induced the phosphorylation of JNK and p-38 MAPK. Treatment with the p-38-specific inhibitor recovered the claudin-1 expression and migration ability of CCA cells. This work demonstrated the potential anticancer effects of andrographolide, indicating that andrographolide could inhibit CCA cell migration via suppression of claudin-1 through the activation of p-38 MAPK signaling pathway. This compound would be useful for development of alternative therapeutic agent for CCA.